Effects of duodenal amino acid infusion on small intestinal starch digestion in cattle - Brake, Derek William (Kansas State University, 2012)
Previous data suggest that greater amounts of postruminal protein increase small intestinal starch digestion in cattle. Duodenally and ileally cannulated steers were used in 5 studies to measure responses in small intestinal starch digestion to amino acids (AA) or casein. Flows of starch to the ileum from the diet were small. Small intestinal starch digestibility was 34.0% when raw cornstarch was continuously infused into the duodenum. Infusion of casein linearly increased (P ≤ 0.05) small intestinal starch digestibility, and small intestinal starch digestion adapted to infusion of casein in 6 d. Ethanol-soluble starch and unpolymerized glucose flowing to the ileum increased linearly (P ≤ 0.05) with increasing infusion of casein. Plasma cholecystokinin was not affected by casein infusion, but circulating levels of glucose increased linearly (P ≤ 0.05). In another study, 5 steers were fed a low-starch diet and provided continuous duodenal infusion of raw cornstarch in combination with AA or casein in order to measure response of small intestinal starch digestion. Duodenal infusion of casein increased (P ≤ 0.05) small intestinal starch digestion. When a mixture of AA with a profile similar to casein (CASAA) was infused, small intestinal starch digestion was similar (P = 0.30) to casein infusion. Infusion of only non-essential AA tended to increase (P = 0.14) small intestinal starch digestion relative to control; however, infusion of essential AA alone did not affect (P = 0.84) small intestinal starch digestion. Additionally, infusion of casein or essential AA increased ileal flows of ethanol-soluble starch, but non-essential AA alone were not different than the negative control. Duodenal infusion of Glu increased (P ≤ 0.05) small intestinal starch digestion, whereas a mixture of Phe, Trp, and Met (PTM) did not. Neither Glu nor PTM increased ileal flow of ethanol-soluble starch, but Glu and PTM provided together tended (P = 0.07) to increase ileal flows of ethanol-soluble starch. Our data suggest that Glu alone can increase small intestinal starch digestion in cattle similar to casein, but increases in small intestinal starch digestion in response to Glu are not associated with an increase in ileal flows of ethanol-soluble starch.
Keywords: Cattle; Starch digestion; Small intestine; Casein; Animal Sciences (0475); Biology, Animal Physiology (0433); Nutrition (0570)